Associations between social anxiety and avoidance, attachment styles and parental marital status, in late adolescence - Maia, B. Rodrigues (2021)
Introduction: The relation between insecure general attachment and social anxiety has long been established. Objectives: To explore the associations between social interaction and performance anxiety and avoidance, attachment styles, and parental marital status. Methods: 146 Portuguese adolescents, with a mean age of 18.99 years old (SD = .848; range: 18-20), filled in the Social Interaction and Performance Anxiety and Avoidance Scale and the Experiences in Close Relationships-Relationship Structures Questionnaire. Results: Distress/Anxiety was correlated with avoidance attachment to mother and father (rs = .17*, p = .04; rs = .18*, p = .03), to anxious attachment to romantic partner (rs = .21*, p = .01), and to anxious and avoidance attachment to best friend (rs = .25**, p = .00; (rs = .17*, p = .035). Avoidance was significantly correlated with avoidance to father and to romantic partner (rs = .18*, p = .03), and to anxious and avoidance attachment to best friend (rs = .21**, p = .009; rs = .18*, p = .03). A significant difference was found in avoidance attachment to father X2 = 10.246 (4, n = 146), p = .036, by parental marital status, with the adolescents with single/divorced parents presenting a higher mean score (Md = 111.10; Md = 82.93) than the other groups. Conclusions: Distress/anxiety seems to be associated with more close relationships, and a single/divorced status with Avoidance. Longitudinal studies are needed to explore if insecure attachment to parents predicts insecure extra-familiar attachment, and to explore the long-term effects of parental marital status.